(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
It is known that diphthongs are among polyphthongs, known as complex phonetic units of the phonetic system, which are characteristic of a number of Turkic languages of the Kipchak and Oguz groups, as well as Turkic languages and dialects of the Karluk and Uyghur groups, which have undergone the process of Kipchakization. Such complex phonetic units are found not only in the original vocabulary of Turkic languages, but also in words borrowed from Mongolian, Iranian and Arabic languages. Long vowels are characterized by high quality stability, and have a special articulation tension. This natural feature of long vowels contributed to their transformation into an emphase means. Emphatic long vowels are found in interjections, onomatopoeic words and particles. There is no doubt that emphatic long vowels are one of the oldest phenomen in the language, and can be confirmed by the facts of related languages